Historical Reflections & an Economic Approach to LEOs as Infrastructure - Liebenau, Jonathan (Global Governance of Low Earth Orbit Satellites, 2025)
This chapter explores the historical and economic trajectories of LEO satellite development, situating these technologies within broader narratives of infrastructure evolution. It considers the role of state and private investment, market dynamics, and technological innovation in shaping the current landscape. By analyzing LEO systems through the lens of economic infrastructure theory, the chapter highlights strategic lessons for policymakers and investors navigating this rapidly changing domain.